Synthesis and biological activity of 1,3,5-triazino[1,2-a]benzimidazol-2-amines. - Dolzhenko, Anton; Chui, W. (Springer, 2007)
Several 4-substituted 1,3,5-triazino[1,2-a]benzimidazol-2-amines were prepared via cyclization of 2-benzimidazolylguanidine with various reactants. The prototropic tautomerism in the obtained dihydro analogs was investigated. According to the NMR data, the 3,4-dihydro form was found to predominate in DMSO solutions. All tested compounds inhibited the activity of mammalian dihydrofolate reductase. The most active compound was 4,4-dimethyl-3,4-dihydro[1,3,5]triazino[1,2-a]benzimidazol-2-amine (IC50 = 10.9 microM).